No easy day the firsthand account of the mission that killed Osama Bin Laden : the autobiography of a Navy SEAL - Owen, Mark; Maurer, Kevin (Dutton, 2012)
For the first time anywhere, the first-person account of the planning and execution of the Bin Laden raid from a Navy Seal who confronted the terrorist mastermind and witnessed his final moments